Pengaruh Pemberian Edukasi Kesehatan Menggunakan Media Audio Visual Tentang Anemia Terhadap Tingkat Pengetahuan Ibu Hamil. - Tri Kurnialin Rusliana; Hestri Norhapifah; Asih Prasetyarini (Voice of Midwifery, 2023)
The anemia of pregnancy is a body condition with a red blood cell count or hemoglobin (Hb) level <11 g/dl. A common problem in pregnant women with anemia is caused by ignorance in dealing with their health problems and adherence to preventive measures given by health workers, so health education needs to be given to increase knowledge. Audiovisual media is media that contains elements of sound and images that can be seen, such as video. Video is considered 94% capable of facilitating the entry of messages or information into the human soul. It was a quasi-experiment with one group pretest and posttest design. The total sample of 49 pregnant women. Data collection was carried out through a questionnaire, then analysis was carried out with the Wilcoxon statistical test. Based on the research results, it is known that there were an effect of providing health education using audio-visual media about anemia on the level of knowledge of pregnant women, where P-Value = 0.000 < Î± 0.05 so that Ha is accepted. It can be concluded that health education using audio-visual media about anemia has a positive impact on pregnant women by increasing knowledge of pregnant women who receive health education.